ALTERNATIF PENGGUNAAN AGREGAT HALUS BATU KAPUR MANTUP DALAM CAMPURAN ASPAL PANAS AC-WC - M.Deny Irawan Budianto; Zulkifli Lubis (U Karst, 2020)
Asphalt Concrete Wearing Course (AC-WC) is a stringent streak which located on the top and the function of it as the outside streak that the thick is 4 centimeters. AC – WC material consists of soft aggregate, crude aggregate, filter, and asphalts. The articles must be tested for identifying the feature. This research is using the Marshall Test method, VIM (%), VMA (%), VIMA (%), VFWA (%), Stabilities (kg), Flow and Marshall Quotient (%). This research was carried out at Lamongan Moslem University’s laboratory. The purpose of this research is to compare the results that have been obtained in research with the existing terms and specifications. The conclusion of this research is the addition of variation in smooth limestone blend 25%, 50%, 75% from the aggregate weight. The top-level increment of Marshall Stability’s showed 33.07% based on the compound 75%; the highest Flow is 3.57% based on the compound 50%, Void in the Mix which was included into the highest specification is 7.49% based on the compound 0%, the top-level increment Void Filled with Asphalt is 85.22% based on the compound 75%, the advance of Marshall Quotient is 29.63% based on compound 75%.Asphalt Concrete Wearing Course (AC-WC) merupakan lapisan perkerasaan yang terletak paling atas dan berfungsi sebagai lapisan aus dengan tebal biasanya 4 cm. Bahan AC –WC terdiri dari Agregat halus, Agregat kasar, bahan pengisi (filler) dan aspal. Bahan – bahan tersebut harus di uji terlebih dahulu untuk mengetahui sifat – sifatnya. Dalam penelitian ini metode yang di gunakan adalah metode marshall : VIM (%), VMA (%), VIMA (%), VFWA (%), Stabilitas (kg), Flow dan Marshall Quotien (%). adapun penelitian di laksanakan pada Laboratorium Universitas Lamongan. Kesimpulan penelitian ini adalah Penambahan variasi campuran batu kapur halus sebesar 25%, 50%, 75% dari berate agregat halus pada penelitian ini menunjukkan kenaikan nilai stabilitas Marshall (Marshall Stability) tertinggi sebesar 33,07% pada campuran75%, kelelahan plastis (Flow) tertinggi sebesar 3,57% pada campuran 50%, rongga  dalam  campuran  (Void in the Mix)   yang  masuk  dalam  spesifikasi angka tertinggi sebesar 7,49% pada campuran 0%, rongga terisi aspal  (Void Filled With Asphalt) kenaikan tertinggi sebesar 85,22% pada campuran 75%, rongga dalam agregat (Void In Mineral Aggregate) menurun sebesar 16,11% pada campuran 75%, serta Marshall Quotient meningkat sebesar 29,63% pada campuran75%.